دور الابتكار في تحقيق الميزة التنافسية للشركات - لقريد حياة; مفتاح الزهرة; ديوان نجاة (جامعة الوادي eloued of university, 2025)
"الملخص تهدف هذه الدراســة إلى التعرف على دور الابتكار في تحقيق الميزة التنافســية للشركات، في ظل التحولات المتســـارعة في بيئة العمل وتم الاعتماد على المنهج الوصفـــي التحليلي، من خلال اســـتبيان شمل عينة من أصــحاب وموظفي الوكالات الســــــــــياحية بالوادي لدراســــــــــة العلاقة بن أبعاد الابتكار (الابتكار الإداري، الابتكار التقني، الابتكار التكنولوجي، الابتكار التسويقي) وتحقيق الميزة التنافسية بالوكالات السياحية، حيث كان حجم العينة43 فردا كوكالة الشنة ويونس ولوس وغيرها وتم قبول 34استبيان صالح للدراسة وتم تحليل البيانات الواردة في الاستبانات عن طريق استخدام البرنامج الإحصائي spssv25الاحصائية للعلوم الاجتماعية،وتوصلت الدراسة لمجموعة من النتائج أهمها: أن هناك علاقة ذات دلالة احصائيةبين الابتكار بأبعاده ( التنظيمي، التقني،التسويقي، اللامركزي ) والميزة التنافسية. وفي نهاية الدراسة توصلنا إلى العديد من التوصيات أهمها: ضرورة تبني الابتكارباعتباره الركيزة الأساسية التي تقوم عليها الوكالات السياحيةلاكتساب الميزة التنافسية. الكلمات المفتاحية:ابتكار، ميزة تنافسية، وكالات سياحية، الوادي. "Abstract This study aims to identify the role of innovation in achieving competitive advantage for companies, in light of the rapid transformations in the work environment. The descriptive-analytical method was adopted through a questionnaire that targeted a sample of owners and employees of travel agencies in El OuedSuch as El-Chenna Agency, Younes Agency, Lous Agency, and others, in order to examine the relationship between the dimensions of innovation (administrative innovation, technical innovation, technological innovation, and marketing innovation) and the achievement of competitive advantage in travel agencies. The sample consisted of 43 individuals, with 34 valid questionnaires accepted for analysis. The data collected was analyzed using the SPSS v25 statistical software for social sciences. The study reached several findings, most notably the existence of a statistically significant relationship between innovation in its dimensions (organizational, technical, marketing, and decentralized) and competitive advantage. At the end of the study, several recommendations were made, the most important of which is the need to adopt innovation as the fundamental pillar upon which travel agencies rely to gain a competitive advantage. Keywords: Innovation, Competitive Advantage, Tourism Agencies, El-Oued.
ماستر علوم اقتصادية
Keywords: الابتكار; الميزة التنافسية; للشركات